Geopolitical Risk and Renewable Energy Equity Markets through Energy Commodity Price Connectedness - Kerem Öztürk; Emirhan Yıldız; Sena Aydın; Ayşe Nur Çelik; Elif Şahin; Mert Demir (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2025)
This study examines whether geopolitical risk (GPR) transmits to renewable energy equity markets through an energy commodity price mediation channel, 717 daily observations from February 24, 2022 to December 31, 2024. Employing the Quantile Time-Varying Parameter Vector Autoregression (QTVP-VAR) connectedness framework, this study incorporates European natural gas prices (TTF), Brent crude oil, and three renewable energy indices — ECO, ERIX, and SPCE — to examine tail-dependent risk transmission across bearish (τ = 0.05), median (τ = 0.50), and bullish (τ = 0.95) market states. Results reveal that total connectedness escalates from 17.1% at the median to 52.3% at the upper tail, confirming pronounced asymmetric risk transmission absent in conventional mean-based frameworks. TTF emerges as the dominant mediating channel, while direct GPR-to-equity transmission remains secondary. SPCE exhibits the highest tail sensitivity among renewable indices. Findings offer critical implications for portfolio risk management, regulatory capital requirements, and European energy policy design.